Entrustable professional activities: report on the implementation experience in a pediatric emergency medicine fellowship program - Gouveia de Aguiar, Gabriel; Bertoni da Silva Jorge, Aline; Angelim Soares Cardoso, Clarisse; Andrade Gomes, Luisa; Quina Albert, Patricia; Detregiachi Neto , Edson (LAJEC - Latin American Journal of Emergency Care, 2024)
-